'Pilgrimage of the Poor': Religious, Social and Political Dimensions of a Moroccan Local Pilgrimage. Issue 1 (1st June 2022) - Al-Ajarma, Kholoud
Abstract: Pilgrimage destinations other than the Ka'aba in Mecca are a contested subject amongst Muslims. For the Moroccan 'poor', who are unable to perform the Meccan pilgrimage, a local pilgrimage known as the Hajj al-Miskin or the 'Pilgrimage of the Poor' is performed as an alternative spiritual journey. In this article, I discuss this pilgrimage at two sites in Morocco. Approaching Islam as a lived religion, I discuss how Moroccans navigate between religious considerations and the realities of everyday life. I argue that the Pilgrimage of the Poor plays a key role in the lives of the pilgrims at both the individual and community level. The debate about the Pilgrimage of the Poor reveals how different groups of Muslims negotiate their positions with respect to different interpretations of the global discursive tradition of Islam, applying these interpretations within their local context.